2017
DOI: 10.1161/hypertensionaha.116.08749
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Arch Pulse Wave Velocity Assessed by Magnetic Resonance Imaging as a Predictor of Incident Cardiovascular Events

Abstract: The predictive value of aortic arch pulse wave velocity (PWV) assessed by magnetic resonance imaging (MRI) for cardiovascular disease (CVD) events has not been fully established. The aim of the present study was to evaluate the association of arch PWV with incident CVD events in MESA. Aortic arch PWV was measured using MRI at baseline in 3,527 MESA participants (mean age = 62 ± 10 years at baseline, 47% male) free of overt CVD. Cox regression was used to evaluate the risk of incident CVD (coronary heart diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 35 publications
4
51
0
6
Order By: Relevance
“…Normal values for PWV (< 10/ms) and central systolic BP (< 130 mmHg) have been described and their predictive value for incident cardiovascular mortality and HF has been demonstrated ( Table ) …”
Section: Methods To Assess Ventricular–arterial Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal values for PWV (< 10/ms) and central systolic BP (< 130 mmHg) have been described and their predictive value for incident cardiovascular mortality and HF has been demonstrated ( Table ) …”
Section: Methods To Assess Ventricular–arterial Couplingmentioning
confidence: 99%
“…Increased PWV was related with reduced coronary flow reserve in CAD patients even after successful revascularization and with elevated N‐terminal pro BNP (NT‐proBNP) post‐myocardial infarction ( Table ) . Myocardial strain imaging (LV GLS < 20%) has shown to detect subclinical dysfunction in CAD patients and represents a more sensitive method of identifying LV performance . Increased aortic stiffness impairs LV function, mainly in the longitudinal axis, through inappropriate VAC with mechanisms discussed in detail above ( Figure ).…”
Section: Ventricular–arterial Coupling In Coronary Artery Diseasementioning
confidence: 99%
“…Arterial stiffness is a common pathological change in hemodialysis patients and is involved in the high morbidity of cardiovascular events. 20) Therefore, finding a simple and effective marker of arterial stiffness may help reducing cardiovascular morbidity in hemodialysis patients. 21,22) Previous studies have shown that traditional cardiovascular risk factors play some roles in the progression of arterial stiffness before development of ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Phase‐contrast MRI (PC‐MRI) enables accurate noninvasive measurement of aortic pulse‐wave velocity (PWV), considered to be the most validated marker of central aortic stiffness . PC‐MRI computed PWV allows for segment‐specific analysis of vascular stiffness, and considers the heterogeneity in vessel wall composition, vessel branching, and backward wave reflections, all typically unevaluated in tonometry‐based studies . Importantly, central aortic and MPA stiffness assessed by PWV have been shown to be prognostic of cardiovascular events with respect to both systemic and pulmonary vasculatures, including hypertension, atherosclerosis, and aneurysmal processes .…”
mentioning
confidence: 99%
“…12,13 PC-MRI computed PWV allows for segment-specific analysis of vascular stiffness, and considers the heterogeneity in vessel wall composition, vessel branching, and backward wave reflections, all typically unevaluated in tonometry-based studies. 12,[14][15][16] Importantly, central aortic and MPA stiffness assessed by PWV have been shown to be prognostic of cardiovascular events with respect to both systemic and pulmonary vasculatures, including hypertension, atherosclerosis, and aneurysmal processes. 17,18 Consequently, PC-MRI derived PWV in patients with a history of KD may provide more specific information on arterial health status and improve the prognostic ability of vascular stiffness in this patient population.…”
mentioning
confidence: 99%